Review of boundary model studies in the Venusian and Martian induced magnetosphere - Jiaqi Zhang; Ming Wang; Haoyang Sui; Zijian Guan; Jinyu Li; Kehan Du; Jianyong Lü (地球与行星物理论评)
Although Venus and Mars do not have a global magnetic field but have atmospheres and ionospheres. During their coupling with the solar wind, the induced magnetospheres are created, as well as the boundaries of the bow shock and the magnetic pileup boundary. These boundaries not only reflect the upstream solar wind conditions but also reveal the state of the planetary space environment. Hence, on the one hand, the modeling of these boundaries can help to understand the basic process of solar wind-planet space interaction. On the other hand, these boundary models can also provide more accurate data on the location of the boundaries for planetary exploration and lay a theoretical foundation for China's "Tianwen-1" program and the corresponding deep space explorations. In addition, these boundary model studies also give important insights into the evolution and development of Earth-like planets. It is shown that the dynamic pressure of the solar wind, the interplanetary magnetic field, the crustal magnetic field, and the solar extreme ultraviolet radiation are all key factors affecting the location of the Martian magnetic pileup boundary, and thus they also affect the shape and size of the Martian bow shock. In addition, the effect of magnetosonic Mach number on the Martian bow shock cannot be neglected. As for the Venusian bow shock, the magnetosonic Mach number is the main controlling factor. Based on the results of the influence of the above parameters, scientists have established relevant boundary models. In this paper, we review the research progress on the Venusian and Martian bow shock and magnetic pileup boundary models, providing reference for planetary science research and deep space exploration.